2015
DOI: 10.1039/c5ra17488k
|View full text |Cite
|
Sign up to set email alerts
|

Recent applications of the hetero Diels–Alder reaction in the total synthesis of natural products

Abstract: The synthetic utility and potential power of the Diels–Alder (D–A) reaction in organic chemistry is evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(50 citation statements)
references
References 558 publications
(616 reference statements)
0
50
0
Order By: Relevance
“…32 We are interested in the asymmetric synthesis, [35][36][37][38][39][40][41][42][43] and applications of named reactions in the total synthesis of natural products which usually use asymmetric synthesis in one or more steps in their multi-step synthesis. [44][45][46][47][48] Due to the increasing number of articles published concerning asymmetric 1,4-addition reactions, catalyzed by Rh-complexes, we were prompted to update the invaluable review by Hayashi et al in 2003. 32 Herein we highlight the recent advances in Rhcomplex asymmetric catalyzed 1,4-addition reactions from 2003 to date.…”
Section: Introductionmentioning
confidence: 98%
“…32 We are interested in the asymmetric synthesis, [35][36][37][38][39][40][41][42][43] and applications of named reactions in the total synthesis of natural products which usually use asymmetric synthesis in one or more steps in their multi-step synthesis. [44][45][46][47][48] Due to the increasing number of articles published concerning asymmetric 1,4-addition reactions, catalyzed by Rh-complexes, we were prompted to update the invaluable review by Hayashi et al in 2003. 32 Herein we highlight the recent advances in Rhcomplex asymmetric catalyzed 1,4-addition reactions from 2003 to date.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, our research group showed interest and focused on the applications of name reactions in the total synthesis of natural products . Among them, in 2012 we published a report, covering the applications of SMCR in the total synthesis of natural products in Tetrahedron, which has seemingly attracted much attention of synthetic organic chemists due to numerous citations it has gained till date.…”
Section: Introductionmentioning
confidence: 99%
“…Hetero-Diels–Alder reactions are considered to be a powerful methodology widely explored for the synthesis of six-membered heterocycles [12] with numerous applications for the construction of complex molecules including naturally occurring products [34], drugs [56], agrochemicals [7], etc. In addition, asymmetric hetero-Diels–Alder reactions are of current interest [810].…”
Section: Introductionmentioning
confidence: 99%